WISC-III subtest patterns of ADHD and normal samples - Snow, J B; Sapp, G L (Psychological reports, 2000)
WISC-III subtest patterns of children with Attention Deficit Hyperactivity Disorder were compared with two other groups of children described in the WISC-III manual, a sample with Attention Deficit Hyperactivity Disorder and the WISC-III standardization sample. Subtest patterns of primary interest were the SCAD Index based on Symbol Search, Coding, Arithmetic, Digit Span, Bannatyne scores for Spatial, Verbal Conceptualization, Sequencing Ability, and the ACID Profile including Arithmetic, Coding, Information, and Digit Span. Comparisons of WISC-III scaled scores and subtest patterns for the samples with Attention Deficit Hyperactivity Disorder supported the congruence between them. Further, the cumulative percentages of children in the three samples who obtained differences between the SCAD Index and the Perceptual Organization Index were computed. Analysis indicated that 17 of the 35 subjects in the current sample obtained differences of 9 points or greater. The results were substantially different from the WISC-III standardization sample but congruent with the WISC-III sample of children with Attention Deficit Hyperactivity Disorder. These outcomes support the diagnostic utility of WISC-III subtest profile patterns for children with Attention Deficit Hyperactivity Disorder.WISC-III subtest patterns of children with Attention Deficit Hyperactivity Disorder were compared with two other groups of children described in the WISC-III manual, a sample with Attention Deficit Hyperactivity Disorder and the WISC-III standardization sample. Subtest patterns of primary interest were the SCAD Index based on Symbol Search, Coding, Arithmetic, Digit Span, Bannatyne scores for Spatial, Verbal Conceptualization, Sequencing Ability, and the ACID Profile including Arithmetic, Coding, Information, and Digit Span. Comparisons of WISC-III scaled scores and subtest patterns for the samples with Attention Deficit Hyperactivity Disorder supported the congruence between them. Further, the cumulative percentages of children in the three samples who obtained differences between the SCAD Index and the Perceptual Organization Index were computed. Analysis indicated that 17 of the 35 subjects in the current sample obtained differences of 9 points or greater. The results were substantially different from the WISC-III standardization sample but congruent with the WISC-III sample of children with Attention Deficit Hyperactivity Disorder. These outcomes support the diagnostic utility of WISC-III subtest profile patterns for children with Attention Deficit Hyperactivity Disorder.